Organizational commitment building to the principal of the senior high school - Ratna Budiarti; Bedjo Sujanto; Mukhneri Mukhtar (International Journal of Evaluation and Research in Education (IJERE), 2022)
This quantitative study aimed to determine the effect of personality and decision-making on the commitment of principals from high schools in the state of DKI Jakarta, Indonesia. The survey method was used in this study, along with path analysis for testing hypotheses. This was done with 89 random selection principals as respondents. This study revealed that personality has a direct positive influence on organizational commitment. There is a positive direct decision-making influence on organizational commitment. Hence, there is also an indirect influence on organizational commitment through decision-making. This paper can be a reference to improving the quality of the school by having a principal who has a strong commitment to his school, supported by a brave personality to get out of his comfort zone and is ready to sacrifice for the school’s progress.